PENGARUH PERGANTIAN MANAJEMEN, OPINI GOING CONCERN, DAN TINGKAT PERTUMBUHAN PERUSAHAAN TERHADAP AUDITOR SWITCHING PADA PERUSAHAAN SEKTOR KEUANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ni Wayan Lesya Pratiwi; Ketut Tanti Kustina (Jurnal Ilmiah Akuntansi & Bisnis, 2018)
The Influence of Management Replacement, Going Concern Opinion and Level of Company Growth to Auditor Switching: Case Study of Financial Sector Companies Listed on the Indonesia Stock Exchange in 2014 – 2017.The issue of Independency is the main problem of Auditor exchange or The Auditor Accounting Office (Auditor Switching) that usually as a mandatory in Indonesia.   The auditor switching is also take place compulsorily because of the government regulations that require auditor rotation, not only in mandatory rotation but also happen as voluntary.  Some various arguments arise when the company doing the auditor rotations voluntary or Accounting Office Company, due to this case happens outside of the regulations of auditor switching that already set by the government. The purpose of this research is to determine the effect of the management replacement, going concern opinion and the level of company growth towards to auditors switching, especially to companies that conduct the auditor rotation voluntary. This research is using the financial data report of Financial Sector Companies that listed on The Indonesia Stock Exchange (IDX) in 2014 – 2017. The method of data collection is by purposive sampling method, which is based on pre-determined criteria.  The hypothesis on this research was tested by using the logistic regression analysis method. The result of this research showed that the management exchange variables, going concern opinion and the level of company growth was positively influenced to the auditor switching.Keywords: Auditor switching, management exchange, going concern opinion, level of company growth, mandatory, voluntary.